2012
DOI: 10.1364/boe.3.002907
|View full text |Cite
|
Sign up to set email alerts
|

Elliptically polarized light for depth resolved optical imaging

Abstract: It is shown that using elliptically polarized light permits selecting well-defined subsurface volumes in a turbid medium. This suggests the possibility of probing biological tissues at specific depths. First, we present the method and preliminary results obtained on an Intralipid phantom. We next report on the method’s performance on a biological phantom (chicken breast) and, finally, on the exposed cortex of an anesthetized rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…To improve the final image, recent studies have suggested the interest of generalizing Linear Polarization Gating (LPG) with the use of elliptical polarization, i.e., Elliptical Polarization Gating (EPG) [19,[33][34][35]. In particular, EPG present two main benefits when compared with LPG.…”
Section: Polarization Gating Techniquesmentioning
confidence: 99%
“…To improve the final image, recent studies have suggested the interest of generalizing Linear Polarization Gating (LPG) with the use of elliptical polarization, i.e., Elliptical Polarization Gating (EPG) [19,[33][34][35]. In particular, EPG present two main benefits when compared with LPG.…”
Section: Polarization Gating Techniquesmentioning
confidence: 99%
“…These results highlight the ability to probe different tissue depths with light polarized elliptically at different angles (polarization gating), yielding images with unique features. While the exact probed depth in this study was not measured, it was previously shown that large angles probe deeper into tissue [35,36]. Depth was also shown to be a function of medium optical properties (Ref.…”
Section: Resultsmentioning
confidence: 81%
“…Recently, it has been shown that selective depths of tissue layers can be probed by tuning the ellipticity of polarization. This effect was demonstrated numerically by Monte Carlo simulation, and was validated experimentally via phantom and rodent measurements [35,36]. Thus, elliptical polarization was adopted here to allow increased depth contrast of hidden object images and to suppress both illumination effects and backscattering phenomena.…”
Section: Polarization: Basic Conceptsmentioning
confidence: 83%
See 2 more Smart Citations